Non-canonical hepatic androgen receptor mediates glucagon sensitivity in female mice through the PGC1α/ERRα/mitochondria axis - Jie Chen; Yuanyuan Wu; Wanyu Hao; Jia You; Lianfeng Wu (Cell Reports)
Summary: Glucagon has recently been found to modulate liver fat content, in addition to its role in regulating gluconeogenesis. However, the precise mechanisms by which glucagon signaling synchronizes glucose and lipid metabolism in the liver remain poorly understood. By employing chemical and genetic approaches, we demonstrate that inhibiting the androgen receptor (AR) impairs the ability of glucagon to stimulate gluconeogenesis and lipid catabolism in primary hepatocytes and female mice. Notably, AR expression in the liver of female mice is up to three times higher than that in their male littermates, accounting for the more pronounced response to glucagon in females. Mechanistically, hepatic AR promotes energy metabolism and enhances lipid breakdown for liver glucose production in response to glucagon treatment through the peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1α)/estrogen-related receptor alpha (ERRα)-mitochondria axis. Overall, our findings highlight the crucial role of hepatic AR in mediating glucagon signaling and the sexual dimorphism in hepatic glucagon sensitivity.